2017
DOI: 10.1016/j.biocon.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Partial migration links local surface-water management to large-scale elephant conservation in the world's largest transfrontier conservation area

Abstract: Successful conservation of large mammals requires vast areas to maintain viable populations. This often requires to embrace large-scale approaches that extend beyond the borders of formally protected areas. However, the quality of the scientific knowledge about animal movement across large conservation areas vary, and could limit the effectiveness of conservation efforts. Here we used GPS tracking to conduct the first study of large-scale movements of African elephants (Loxodonta africana) in Hwange NP (Zimbab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…Many threatened species, particularly those prone to conflict with humans, are confined within relatively small and increasingly isolated protected areas surrounded by human‐dominated landscapes (Graham et al 2009, Bauer et al 2015). The small and scattered nature of these protected areas is of particular concern for the management and conservation of species that naturally move, migrate, or disperse over large areas (Durant et al 2017, Tshipa et al 2017). Therefore, efforts have been made to protect contiguous natural areas to preserve vital connections between protected areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many threatened species, particularly those prone to conflict with humans, are confined within relatively small and increasingly isolated protected areas surrounded by human‐dominated landscapes (Graham et al 2009, Bauer et al 2015). The small and scattered nature of these protected areas is of particular concern for the management and conservation of species that naturally move, migrate, or disperse over large areas (Durant et al 2017, Tshipa et al 2017). Therefore, efforts have been made to protect contiguous natural areas to preserve vital connections between protected areas.…”
mentioning
confidence: 99%
“…Therefore, efforts have been made to protect contiguous natural areas to preserve vital connections between protected areas. But empirical information on movement patterns, dispersal, and connectivity is lacking for many of the wide‐ranging species for which these larger protected areas have been created (Tshipa et al 2017). This lack of information prevents a thorough assessment of the effectiveness of protected areas for species persistence and potentially limits their development.…”
mentioning
confidence: 99%
“…Tshipa et al . ), sleep (Savage & West ), heat (Humphries & Careau ) and shelter (Eggleston & Lipcius ). Less obvious physiological processes requiring recharge that transcend the individual level may include activities such as reproduction (Proaktor et al .…”
Section: Methodsmentioning
confidence: 99%
“…River basins that encompass natural parks must develop water management plans that consider the impact of human activities on water availability and quality for animal populations. Tshipa et al (2017) found that elephant migration patterns shift depending on resource availability, as evidenced by elephants changing behaviors to incorporate man-made watering holes in the Kavango-Zambezi Transfrontier Conservation Area (TFCA). The authors tracked elephant movements to determine their wet-dry season ranges, and found that surface water availability increased the likelihood of seasonal migration.…”
Section: Transboundary Water Governance In Protected Natural Areasmentioning
confidence: 99%
“…The authors tracked elephant movements to determine their wet-dry season ranges, and found that surface water availability increased the likelihood of seasonal migration. Water-driven migration is not unique, as also evidenced by zebra and wildebeest populations in Tanzania; however, the impact of artificial watering holes on elephant migration patterns highlight the importance of human water management decisions on the natural habitat (Tshipa et al, 2017;Morrison et al, 2016). Therefore, a regional water governance system should be able to adapt to changes in water availability (i.e.…”
Section: Transboundary Water Governance In Protected Natural Areasmentioning
confidence: 99%